Agility performance with and without ball during a novel football-specific video stimulus test in junior players - Savolainen, E.; Vänttinen, T.; Ahtiainen, J. P. (19th International Symposium "Modern Science and Practice for Strength and Endurance Training" October 10-12, 2018, 2020)
Agility has been defined as rapid whole body movement with change of speed and/or direction in response to stimulus. Agility performance is affected by cognitive, physical and technical qualities. The purpose of this study was to investigate the role of physical and cognitive qualities to football-specific agility performance in players of different ages.